2021
DOI: 10.1186/s13018-021-02698-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for perioperative hidden blood loss in unilateral biportal endoscopic spine surgery: a retrospective multicenter study

Abstract: Background Hidden blood loss (HBL) represents an important complication of unilateral biportal endoscopic (UBE) spine surgery. This study aimed to evaluate HBL and its possible risk factors among patients undergoing UBE surgery for lumbar degenerative diseases. Methods This multicentric retrospective study was conducted in 3 different medical centers between July 2020 and April 2021. Data of patients who underwent UBE surgery were extracted by elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
8
24
0
Order By: Relevance
“…However, the partial laminotomy employed in UBE technique may have caused bleeding of cancellous bone. Our findings were consistent with those of Wang et al [ 27 ] who reported a 469.5 mL of HBL following UBE surgery. However, their study included patients with lumbar degenerative diseases, including LDH, lumbar stenosis, and spondylolisthesis.…”
Section: Discussionsupporting
confidence: 93%
“…However, the partial laminotomy employed in UBE technique may have caused bleeding of cancellous bone. Our findings were consistent with those of Wang et al [ 27 ] who reported a 469.5 mL of HBL following UBE surgery. However, their study included patients with lumbar degenerative diseases, including LDH, lumbar stenosis, and spondylolisthesis.…”
Section: Discussionsupporting
confidence: 93%
“…Diagram illustrating the method used to measure the thickness of total soft tissue, paraspinal muscle and subcutaneous layer at the level of L5 through sagittal view on T2-weighted MRI. (7,8), the amount of HBL during surgery was significantly higher than that of VBL. Excessive HBL not only increases the incidence of perioperative complications but also prolongs patient recovery time.…”
Section: Discussionmentioning
confidence: 82%
“…Although previous studies have elaborated on the complications following UBE surgery, spine surgeons have underestimated HBL in UBE surgery. Wang et al ( 8 ) retrospectively analyzed patients who underwent UBE surgery and reported an HBL volume of 469.5 ± 195.3 ml, accounting for 57.6% of TBL. Age, number of fusion levels, ASA classification, surgery time, PBV, TBL, postoperative Hct, Hct loss, and fibrinogen level were independent risk factors for HBL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interference of lumbar paraspinal muscles in UBE has attracted increasing attention from researchers [10][11][12]. Ahn Jae-Sung found that significant postoperative changes in the paraspinal muscles of UBE surgery by comparing the MRI scans [13].…”
Section: Discussionmentioning
confidence: 99%